Effect of heat treatment on the corrosion behavior of SS316 stainless steel in simulated body environment - Mohd Asyraf, Che Azmi (2010)
This thesis is entitled about the effect of heat treatment on corrosion behavior on SS316 stainless steel in simulated body environment. Biomedical materials are very important in the modern world to manufacture the variety of prosthetic devices which are the artificial replacements for human body. These artificial replacements are use in a biological system such as the human body in an effort to provide the function of the original parts. When a metal device is implanted into human body, it is continually exposed to extracellular tissue fluid. This interaction can lead to either failure of the implant or have an adverse effect on the patient resulting in the rejection of the implant by the surrounding tissue or both. The objective of this project is to investigate the effect of stress relief on corrosion behavior of SS316 stainless steel in simulated body fluid. Stress relief had been performed to the sample with two different time and temperature. Stress relief is used to relieve stresses that remain locked in a structure as a consequence of a manufacturing sequence such as machining. The sample was prepared for electrochemical test. Electrochemical tests using a potentiostat WPG1000 have also been conducted and reported in this thesis. The corrosion rates of the alloys were then compared.